PEKEN BANYUMASAN EDISI TJILATJAP: TJAKRAWEDANA 1, IMPLEMENTASI KONSEP CREATIVE PLACEMAKING DI KABUPATEN CILACAP - Ilahi, Novita Asma; Musyafiq, Afrizal Abdi (Universitas PGRI Yogyakarta, 2023)
This community service activity collaborated with various elements of academia, including Lecturers at the Cilacap State Polytechnic (PNC) and Lecturers at the Telkom Purwokerto Institute of Technology (ITTP) and industrial elements around Cilacap Regency. This activity held in a historic building, aims to form a sustainable creative ecosystem by creating creative placemaking as a platform to improve the creative industry and increase the post-pandemic economy in Cilacap Regency. The method of this activity begins with the selection of the main theme H.A.P (Heritage-Art-Pop) as part of the Tjilatjap – Tjakrawedana 1 Edition Banyumasan Peken. The results of this activity were able to collaborate with all parties who are members of B.Y.O.T Heptahelix activities, namely academics, local government, industry, entrepreneurs, media, community, and aggregators. The discussion regarding the development of creative industries in Cilacap Regency is expected to be able to boost the post-pandemic community's economy and be able to alleviate poverty. Keyword: H.A.P; Creative placemaking; Tjakrawedana; Peken Banyumasan; Cilacap Creative